Constructing and reconstructing: An approach to the Peruvian educational system before and after the War of the Pacific - Sánchez Gálvez, José Fernando (2024)
After the War of the Pacific, education became crucial in addressing the lack of patriotism and the perceived “indigenous inferiority”—factors that, according to intellectual critique of the time, had led to the defeat by Chile. This article aims to analyze how the Peruvian state restructured the educational system during the period of National Reconstruction. It explores the challenges and approaches of Peruvian schooling throughout the nineteenth century. By examining the development of educational institutions up to 1879, it seeks to understand the reconstruction process in the post-war years until the late nineteenth century. Analyzing education in these periods allows us to understand its role during the foundational moments of the Republic.